Analysis of the relationship between elite wrestlers` leg strength and balance performance, and injury history - Çimen Polat, S.; Bulgay, C.; Yarim, I.; Cicioglu, H. I.; Çetin, E. (Sports, 2018)
The purpose of this study is to examine the correlation between leg power and balance performance in elite wrestlers and injury history. In the research group, there are 18 elite freestyle male wrestlers at the ages of 24.27 ± 3.18 years, with a height of 171.86 ± 5.44 cm and a body weight of 79.27 ± 11.16 kg. Information on the injury history of the athletes` upper legs for the past year was collected via interviews with the club`s physiotherapist. Laboratory tests to measure performance assessed height, body weight, Y balance and isokinetic leg strength. Data obtained from the study are presented as mean and standard deviation. The test of normality was carried out by the Shapiro-Wilk test. The Pearson Correlation Test was performed for all parameters with normal distribution, and significance level was accepted as p < 0.05. It was found that there is a relationship between the wrestlers` right leg ratio and hamstring strength and injury history. However, there is no statistically significant relationship between left leg hamstring, quadriceps, ratio, right leg quadriceps, or right and left leg balance performance, and injury history. The resulting data shows that the proportioning between hamstring and quadriceps muscles in freestyle wrestlers` upper leg strength values is not ideal. This finding provides evidence that injury risk increases with the additional impact of loss of strength.